Mobile banking usage, quality of growth, inequality and poverty in developing countries - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2017)
The transition from Millennium Development Goals to Sustainable Development Goals has substantially shifted the policy debate from development to inclusive development. Using interactive quantile regressions, we examine the correlations between mobile banking and inclusive development (quality of growth, inequality and poverty) among individuals in 93 developing countries for the year 2011. Mobile banking entails: `mobile used to pay bills' and `mobile used to receive/send money'. The findings broadly show that increasing mobile banking dynamics to certain thresholds would increase (decrease) quality of growth (inequality) in quantiles at the high-end of inclusive development distributions for the most part. The study is original in that it explores the relationship between mobile banking and inclusive development using three measurements of inclusive development, namely: quality of growth, inequality and poverty. As a main policy implication, encouraging mobile banking applications would play a substantial role in responding to the challenges of immiserizing growth, inequality and poverty in developing countries.
Keywords: G20; O40; I10; I20; I32; 330; Mobile banking; Quality of growth; Poverty; Inequality; Developing countries